Key Role of Obesity in Genitourinary Tumors with Emphasis on Urothelial and Prostate Cancers - Santoni, Matteo (Cancers (Basel), 2019)
Background: In human populations, a certain amount of data correlate obesity/body mass index (BMI) with urothelial cancer (UC) and prostate cancer (PCa) occurrence, however this is not fully elucidated at all stages of disease. In an attempt to shed light on uncertain areas in such field, in the present review we illustrate the main molecular mechanisms linking obesity and cancer, focusing on the correlation between obesity and tumor risk, disease progression and response to chemo- and immunotherapy in patients with UC and the predictive/prognostic role of obesity in PCa patients treated with the currently available therapeutic approaches. Methods: We did a large-scale literature search on existing scientific websites focusing on keywords “obesity”, “body mass index (BMI)”, “urothelial cancer”, “prostate cancer”, “docetaxel”, “cabazitaxel”, “abiraterone acetate”, “enzalutamide”, and “radium223”. Results: Many adipocytes-induced molecules support tumor proliferation through activation of various cellular pathways. The available evidence in the postoperative setting do the role of BMI in oncological outcomes prediction still not completely clear. Likewise, in metastatic UC patients controversial results link the role of obesity/BMI with clinical outcomes of tumor response to chemotherapy. Adipose stromal cells recruitment, induced by PCa cells, from white adipose tissue to the tumor sites inducing cell invasiveness was associated with poor survival. Conflicting data, although more oriented towards a better survival outcome, resulted in obese patients treated with docetaxel. In PCa cell-lines a certain cabazitaxel chemo resistance adipose stromal cells (ASC)-mediated was demonstrated. In metastatic castration-resistant PCa patients with high BMI (>25 kg/m(2)) receiving abiraterone acetate there were significant worse survival outcomes, while in enzalutamide patients BMI did not affect survival outcome. In radium 223 patients higher BMI significantly correlated with favorable overall survival. Conclusions: The main focus of this review was to understand the interplay between obesity/BMI and UC/PCa. Several pathogenic cellular pathways exploring the issue are discussed, opening the way to challenging tailored treatments on the basis of BMI. Improving the knowledge of molecular connections between obesity and UC and PCa could favor the development of new therapies likely reducing chemo- and immunotherapy drug resistance.